Postoperative Achilles Pull-out Strength after Calcaneoplasty for Haglund's Syndrome. Issue 3 (14th September 2018) - Pfeffer, Glenn; Gonzalez, Tyler; Nelson, Trevor; Metzger, Melodie
Category: Hindfoot Introduction/Purpose: Haglund's syndrome involves a prominent posterior superior prominence of the calcaneus, in conjunction with pain caused by local inflammation. Nonoperative management includes orthotic inserts, immobilization, shoe modification and physical therapy. If non-operative management fails, surgical management with calcaneoplasty is often needed. No study has assessed Achilles tendon pull-out strength after a calcaneoplasty for Haglund's syndrome. The purpose of this study was to investigate those changes in a cadaveric model and provide objective data upon which to base postoperative recovery. Methods: 8 matched pairs of cadaveric specimens (mid-tibia to toes) were divided into two cohorts. The matched pairs compared Achilles pull-out strength between intact and open calcaneoplasty specimens. Prior to testing, BMD was determined and lateral X-ray images were obtained before and after surgery to quantify bone removal. The distal aspect of each calcaneus was potted and held at a 20 degree angle. The Achilles tendon was secured in a freeze-clamp, which was attached to a mechanical testing system. Specimens were then loaded to failure. Outcome measures include: Height of bony resection, angle of bone resection, load to failure, and mode of failure. Results: Specimens with open calcaneoplasty had a 45% reduction in strength (failure load: 742 N) compared to their intact counterpart (1341 N), p<0.05. Load to failure was significantly correlated with BMD (r=0.64, p<0.05). Conclusion: Traditional open calcaneus resection demonstrated a potentially catastrophic weakness of the Achilles tendon insertion. Mineral density further affects weakening of the Achilles insertion. . Biomechanical evidence presented above supports the practice of protected weight bearing and cautious return to activity after open calcaneoplasty for Haglund's syndrome.